An audibility model of the headband trial with a bone conduction device in single-sided deaf subjects. - Cattani, Guido; Rhebergen, Koenraad S.; Smit, Adriana L. (International Journal of Audiology, 2024)
Objective: Modelling the head-shadow effect compensation and speech recognition outcomes, we aimed to study the benefits of a bone conduction device (BCD) during the headband trial for single-sided deafened (SSD) subjects. Design: This study is based on a database of individual patient measurements, fitting parameters, and acoustic BCD properties retrospectively measured on a skull simulator or from existing literature. The sensation levels of the Bone-Conduction and Air-Conduction sound paths were compared, modelling three spatial conditions with speech in quiet. We calculated the phoneme score using the Speech Intelligibility Index for the three conditions in quiet and seven in noise. Study sample: Eighty-five SSD adults fitted with BCD during headband trial. Results: According to our model, most subjects did not achieve a full head-shadow effect compensation with the signal at the BCD side and in front. The modelled speech recognition in the quiet conditions did not improve with the BCD on the headband. In noise, we found a slight improvement in some specific conditions and minimal worsening in others. Conclusions: Based on an audibility model, this study challenges the fundamentals of a BCD headband trial in SSD subjects. Patients should be counselled regarding the potential outcome and alternative approaches.